Nanotechnology: an introduction and overview - Meyyappan, M. (Universiti Malaysia Perlis, 2010)
Organized by Universiti Malaysia Perlis, 5th - 7th January 2010 at Brasmana Ballroom, Kuala Perlis, Perlis.